Phase 2 Study of Pomalidomide (CC-4047) Monotherapy for Children and Young Adults With Recurrent or Progressive Primary Brain Tumors - Fangusaro, Jason; Cefalo, Maria Giuseppina; Garré, Maria Luisa; Marshall, Lynley V.; Massimino, Maura; Benettaib, Bouchra; Biserna, Noha; Poon, Jennifer; Quan, Jackie; Conlin, Erin; Lewandowski, John; Simcock, Mathew; et al. (Frontiers in Oncology, 2021)
Introduction Treatment of recurrent primary pediatric brain tumors remains a major challenge, with most children succumbing to their disease. We conducted a prospective phase 2 study investigating the safety and efficacy of pomalidomide (POM) in children and young adults with recurrent and progressive primary brain tumors. Methods Patients with recurrent and progressive high-grade glioma (HGG), diffuse intrinsic pontine glioma (DIPG), ependymoma, or medulloblastoma received POM 2.6 mg/m2/day (the recommended phase 2 dose [RP2D]) on days 1-21 of a 28-day cycle. A Simon’s Optimal 2-stage design was used to determine efficacy. Primary endpoints included objective response (OR) and long-term stable disease (LTSD) rates. Secondary endpoints included duration of response, progression-free survival (PFS), overall survival (OS), and safety. Results 46 patients were evaluable for response (HGG, n = 19; DIPG, ependymoma, and medulloblastoma, n = 9 each). Two patients with HGG achieved OR or LTSD (10.5% [95% CI, 1.3%-33.1%]; 1 partial response and 1 LTSD) and 1 patient with ependymoma had LTSD (11.1% [95% CI, 0.3%-48.2%]). There were no ORs or LTSD in the DIPG or medulloblastoma cohorts. The median PFS for patients with HGG, DIPG, ependymoma, and medulloblastoma was 7.86, 11.29, 8.43, and 8.43 weeks, respectively. Median OS was 5.06, 3.78, 12.02, and 11.60 months, respectively. Neutropenia was the most common grade 3/4 adverse event. Conclusions Treatment with POM monotherapy did not meet the primary measure of success in any cohort. Future studies are needed to evaluate if POM would show efficacy in tumors with specific molecular signatures or in combination with other anticancer agents. Clinical Trial Registration ClinicalTrials.gov, identifier NCT03257631; EudraCT, identifier 2016-002903-25.